SMK Revitalization: Good Governance Efforts of the DKI Jakarta Provincial Government - Widyastuti, Erma; Wahyudi Atmoko, Andreo (Pelopor Publikasi Akademika, 2025)
DKI Jakarta is one of the pioneers in implementing the programme. In fact, the Governor of DKI Jakarta passed a special regulation for this program, which is contained in Governor Regulation Number 32 of 2019 concerning Revitalisation of Vocational High Schools. Therefore, this study aims to analyse the implementation of good governance principles in the implementation of the Vocational High School Revitalisation program by the DKI Jakarta Provincial Government. The research method used is a descriptive method with a qualitative approach. The theory of good governance is the analytical framework in this research. The data collection technique was conducted using a literature study of several literatures, such as journal articles, online news, and official government publications. Data were analysed using three stages, namely data reduction, data presentation, and conclusion drawing. The findings of this study show that the DKI Jakarta Provincial Government has well implemented the principles of transparency as well as the principles of effectiveness and efficiency in the implementation of the DKI Jakarta Vocational Revitalisation program. Meanwhile, the principle of participation has been fulfilled quite well. The principles of accountability and fairness cannot be assessed further. This is due to the lack of progressive reports from the DKI Jakarta Provincial Government regarding the implementation of Revitalisation of Vocational Schools. However, based on the available data, the principle of justice has been implemented quite well. In contrast to the principle of accountability, which seems to be less considered by the DKI Jakarta Provincial Government.